Gender Differences in Digital Literacy Skills and Political Awareness Among Secondary School Students in Gusau Educational Zone, Zamfara State, Nigeria - Sule Muhammad; Haladu Isa Bayero (Penerbit Hellow Pustaka, 2026)
This study investigated gender differences in digital literacy skills and political awareness among secondary school students in the Gusau Educational Zone, Zamfara State, Nigeria. A descriptive survey design was adopted, with a population of 8,753 SS2 students from public schools. Using a stratified random sampling technique, a sample of 365 students was selected. Data were collected through the Digital Literacy and Civic/Political Awareness Questionnaire (DLCPAQ), validated by experts and tested for reliability (Cronbach’s alpha = 0.86). Independent samples t-tests and MANOVA were employed to analyze the data at a 0.05 significance level. Findings revealed a significant difference in digital literacy skills between male and female students, with males demonstrating higher proficiency. Conversely, no significant gender difference was observed in political awareness, indicating that male and female students possessed similar levels of civic and political understanding. The study highlights the role of gender in digital skill acquisition while showing that political awareness is more evenly distributed across genders. The findings underscore the need for targeted interventions to enhance digital literacy among female students and for continued promotion of civic education to foster informed and responsible participation in society.